The Role and Impact of Trust on the Operation and Sustainability of the State - Kis, Norbert (Public Finance Quarterly, 2018)
The foundation for economic growth is the belief of people in a better and happier future. Without this we would not be shopping more and more, we would not take out loans and we would not be after technological innovations. Enhanced economic growth is founded on the increase of confidence in the future, while the contrary, the deadlock of public trust starts a chain reaction toward an economic crisis. Governance has to recognize that it makes the biggest mistake if it “only governs” but fails to give a convincing and encouraging perspective and plans to the people and the companies. The analysis assesses each component of the correlation between security, trust and economy based on the experiences of the Hungarian governance. There is a correlation between the sense of security, the change in security risks and the public trust relating to the governance. The governments and the societies that know how to handle a security crisis and strengthen the sense of security will also be successful in terms of increasing public trust. It is justifiable that only the governments that are able to strengthen the sense of security of the citizens will be successful in economy. If a government underperforms in the “security test”, it will lose public trust regardless of any other positive results. The success factor of the governance of the future: the security of people. The author intends to support these theorems with statistical analyses.